Development Inequality Between Regencies/Cities and Its Impact on Population Migration within the Province of West Nusa Tenggara Period 2020–2024 - Risky Kusumawati; Eka Agustiani (Yayasan Riset dan Pengembangan Intelektual, 2025)
This research examines the influence of development inequality between districts/cities on population migration in West Nusa Tenggara Province (NTB) in 2020–2024. Using a panel data approach and the Fixed Effect Model (FEM) method, The present research examines six independent variables, Gross Regional Domestic Product (GDP) per capita, poverty rate, education level, infrastructure, open unemployment rate, and Human Development Index (HDI), on inward migration as dependent variables. Empirical results based on the Fixed Effect Model estimate show that partially, the variables of infrastructure, unemployment, and HDI have a significant effect on inward migration, while other variables do not. Simultaneously, all independent variables had a significant effect with an adjusted R² value of 70.11%, indicating that the model has a strong ability to explain interregional migration. Based on these results, this study recommends equitable development policies through poverty alleviation based on local empowerment, improving the quality of infrastructure and education, and creating productive jobs to reduce inequality and control unbalanced migration flows between regions.